Statistical analyses of artificial waterpoints: their effect on the herbaceous and woody structure composition within the Kruger National Park - Goodall, Victoria Lucy (Rhodes University, Faculty of Science, Department of Statistics, 2007)
The objective of this project is to link the statistical theory used in the ecological sciences with an actual project that was developed for the South African National Parks Scientific Services. It investigates the changes that have occurred in the herbaceous and woody structure due to the closure of artificial waterpoints; including the impacts that elephants and other herbivores have on the vegetation of the Kruger National Park. This project was designed in conjunction with South African National Parks (SANP) Scientific Services and it is a registered project with this department. The results of this project will be submitted to Scientific Services in accordance with the terms and conditions of a SANP research project. A major concern within the KNP is the declining numbers of rare antelope and numerous projects have been developed to investigate possible ways of halting this decline and thus protecting the heterogeneity of the Kruger National Park. Three different datasets were investigated, covering three aspects of vegetation structure and composition within the KNP. The first investigated the changes that have occurred since the N'washitsumbe enclosure in the Far Northern KNP was fenced off from the rest of the park. The results show that over the 40 years since the enclosure was built, changes have occurred which have resulted in a significant difference in the abundance of Increaser 2 and Decreaser grass species between the inside and the outside of the enclosure. Increaser 2 and Decreaser categories are the result of a grass species classification depending on whether the species thrives or is depressed by heavy grazing. The difference in grass species composition and structure between the inside and the outside of the enclosure indicates that the grazing animals within the KNP have influenced the grass composition in a way that favours the dominant animals. This has resulted in a declining roan antelope population - one of the species that is considered as a 'rare antelope'. Many artificial waterpoints (boreholes and dams) have also been closed throughout the KNP in the hope of resulting in a change in vegetation structure and composition in favour of the roan. Veld condition assessment data for 87 boreholes throughout the Park was analyzed to determine whether the veld in the vicinity is beginning to change towards a more Decreaser dominated sward which would favour the roan. The results were analyzed for the different regions of the Park; and they indicate that changes are becoming evident; however, the results are not particularly conclusive, yet. The majority of the boreholes were closed between 1994 and 1998 which means that not a lot of data were available to be analyzed. A similar study conducted in another 10 years time might reveal more meaningful results. However the results are moving in the direction hoped for by the management of the KNP. The results show that the grass composition has a higher proportion of Decreaser grasses since the closure of the waterpoints, and the grass biomass around these areas has also improved. The results were analyzed on an individual basis; and then on a regional basis as the minimal data meant that the individual analyses did not provide any significant results. A third study was then done on the impact that the rapidly increasing elephant population on the vegetation within the Riparian zone along three rivers in the Far Northern region of the KNP. The riparian zone is an important part of the landscape, in terms of providing food for many animals as well as shade. The elephant population has increased substantially since the termination of the culling program and this means that the feeding requirements of the population has increased which could result in severe damage upon the vegetation, as elephants can be very destructive feeders. The results show surprising differences between the three years of data that were analyzed; however the results indicate that the elephants are targeting specific height ranges of trees when feeding; however they do not seem to consistently target specific tree species. This is positive for the diversity of the Riparian zone as this region is very important both ecologically and aesthetically for the tourists who visit the Park.
Keywords: South African National Parks; Ecology -- Statistical methods; Regression analysis; Log-linear models; Game reserves -- South Africa; Kruger National Park (South Africa)